Comparing the Quality of Life and Hearing Thresholds Following Stapedectomy Versus Laser Stapedotomy with NiTiBOND Piston - Péter Révész; Eszter Kopjár; Zsolt Szakács; Vilmos Warta; Alexandra Csongor; Imre Gerlinger; István Szanyi (Journal of International Advanced Otology)
BACKGROUND: The purpose of this study was to examine the quality of life (QoL) and hearing thresholds of patients who underwent 2 types of stapes surgery.